La tregua (1960), by Mario Benedetti: a reading based on law and literature - Salazar Navarro, Cassandra Michelle (2023)
This brief paper deals with human action in its narrative dimension, materialised in the novel La tregua (1960). It uses the literary theory of law to analyse the life and work of one of the most important writers of 20th century Spanish-American literature: Mario Benedetti. We will be able to understand the intersection of law «in» literature by means of legal concepts and values, associated with labour conditions. Thus, we will demonstrate that in La tregua there is an intrinsic social critique of the historical reality of Montevideo represented in this novel, especially in terms of alienation.